Liver Transplantation for Intrahepatic Cholangiocarcinoma: What Are New Insights and What Should We Follow? - Sun, Dawei; Lv, Guoyue; Dong, Jiahong (Frontiers in Oncology, 2022)
Intrahepatic cholangiocarcinoma (iCCA) is a complex malignancy carrying poor prognosis. Liver transplantation (LT) was historically contraindicated for iCCA, due to poor outcomes after LT. However, increasing researches have challenged this premise, because LT alone or combined with neoadjuvant chemotherapy has achieved relatively satisfactory transplant outcomes in well selected iCCA cases. This current review based on existing clinical researches, evinced that LT might serve as a viable option in iCCA cases as follows: ① unresectable tumor restricted to 2 cm, along with context of chronic liver diseases; ② unresectable tumor locally advanced within the liver (without extrahepatic metastasis or vascular invasion) but responses to tumor down-staging treatments (including systemic neoadjuvant therapy and/or locoregional therapy). On the contrary, it’s recommended as contraindications in iCCA cases as follows: ① patients with tumor progression while waiting for a transplant (increase of diameter, macrovascular invasion, new nodules, escalation of carbohydrate antigen 19-9, or extrahepatic spread); ② patients with iCCA recurrence. Conclusively, tumor burden, tumor biology, and response to down-staging strategies should be taken into consideration before LT. Whereas, the concept of “locally advanced stage” remains to be defined in the future, especially the optimized combination of “maximum size of largest lesion”, “number of lesions”, with/without “tumor differentiation”, just like Milan criteria widely used for hepatocellular carcinoma. Given the scarcity of donor organ, as well as the debate about LT in iCCA, accurate consensus about LT for iCCA patients is still urgently warranted.